Antibodies elicited by yeast glycoproteins recognize HIV-1 virions and potently neutralize virions with high mannose N-glycans. Issue 39 (22nd September 2015) - Zhang, Hong; Fu, Hu; Luallen, Robert J.; Liu, Bingfen; Lee, Fang-Hua; Doms, Robert W.; Geng, Yu
Abstract The glycan shield on the human immunodeficiency virus 1 (HIV-1) envelope (Env) glycoprotein has drawn attention as a target for HIV-1 vaccine design given that an increasing number of potent and broadly neutralizing antibodies (bNAbs) recognize epitopes entirely or partially comprised of high mannose type N-linked glycans. In an attempt to generate immunogens that target the glycan shield of HIV-1, we previously engineered a triple mutant (TM) strain of Saccharomyces cerevisiae that results in exclusive presentation of high mannose type N-glycans, and identified five TM yeast glycoproteins that support strong binding of 2G12, a bNAb that targets a cluster of high mannose glycans on the gp120 subunit of Env. Here, we further analyzed the antigenicity and immunogenicity of these proteins in inducing anti-HIV responses. Our study demonstrated that the 2G12-reactive TM yeast glycoproteins efficiently bound to recently identified bNAbs including PGT125-130 and PGT135 that recognize high mannose glycan-dependent epitopes. Immunization of rabbits with a single TM yeast glycoprotein (Gp38 or Pst1), when conjugated to a promiscuous T-cell epitope peptide and coadministered with a Toll-like receptor 2 agonist, induced glycan-specific HIV-1 Env cross-reactive antibodies. The immune sera bound to both synthetic mannose oligosaccharides and gp120 proteins from a broad range of HIV-1 strains. The purified antibodies recognized and captured virions that contain both complex- and high mannose-type of N-glycans, and potently neutralized virions from different HIV-1 clades but only when the virions were enforced to retain high mannose N-glycans. This study provides insights into the elicitation of anti-carbohydrate, HIV-1 Env-cross reactive antibodies with a heterologous glycoprotein and may have applications in the design and administration of immunogens that target the viral glycan shield for development of an effective HIV-1 vaccine.